Kula Pahari Culture: Local Wisdom and Educational Media to Build Harmony in Central Kalimantan Communities - Firdausi, Muhammad Fikri; Hamdanah, Hamdanah; Miftahurrizqi, Miftahurrizqi (Jayapangus Press, 2025)
Building harmony in cultural and religious diversity needs to be maintained, given the increasing challenges in facing an increasingly globalized life. Therefore, local values such as kula pahari have provided one of the media to build harmony in the community. For this reason, the purpose of this research is how the concept of kula pahari as a medium for social education, the impact of kula pahari on harmony and how the challenges of preserving kula pahari in the modern era. This type of research is descriptive qualitative with data collection techniques interviews and text-related studies in the form of books, journals and other sources. The results of the study show that (a) kula pahari can be used as a medium for social education because this concept teaches a set of norms or rules in society to live in harmony despite differences, by maintaining manners and spiritual morals that prioritize kinship and brotherhood by emphasizing family emotional ties tied by cultural ropes based on a sense of community in the Huma Betang container. (b) the impact of the kula pahari concept as a literacy media, Belom Bahadat Theology (mutual respect and not berating), upholding the principle of ta'awun and optimizing the Community Harmony Institution. (c) challenges to kula Pahari in the modern era such as truth claim culture, political and economic disparities, competition between migrants and natives and differences in social and cultural values. By integrating local wisdom values, the community can strengthen solidarity by spreading educational literacy, upholding mutual respect, helping each other, and organizing religious harmony institutions and community empowerment in Central Kalimantan.